Poda Na Lima As a Learning Model For Independent Learning Curriculum - Silvi Tabah Hati (Universitas Muhammadiyah Enrekang, 2023)
Abstract Poda Na Lima is the advice of elders who have gone down and down for the angkola-mandailing community This paper wants to see the philosophy of Poda Na Lima as a learning model for the independent learning curriculum. The study was conducted for six months. This research was conducted in Batang Baruhar Jae Village located in Gunung Tua-North Sumatra.This type of research is qualitative using a realist ethnographic approach. The Realist ethnographic approach is used by researchers to be able to draw the situation of Ethnic Values in the Angkola-Maindailing community objectively, without being influenced by other elements. Data collection techniques are carried out by observation, in-depth interviews and literature studies that examine directly about Poda Na Lima. Primary data are traditional elders and teachers of Tanjung Malipe State Elementary School (SDN). The results of the study concluded that the philosophy of Poda Na Lima consists of 1) Paias Rohamu (cleanse your heart), 2) Paias Pamatangmu (clean your body), 3) Paias Parabitonmu, (clean your clothes), 4) Paias Bagasmu (clean your house), and 5) Paias Pakaranganmu (clean your yard / environment). Meanwhile, in its implementation, the principle of Poda Na Lima as a learning model of the independent learning curriculum is seen in congregational dhuha prayers and reading the Quran which is done every day is the first aspect (Paias Rohamu). Emphasis on Discipline of Environmental Love, Examination of students who do not bathe from home by BP and Coaching Competition Participants and Talents Student achievement is an aspect of Paias Pamatangmu.Provision or procurement of school media is the third principle (Paias Paribotanmu). While the promulgation of characters and the giving of